2022
DOI: 10.1093/zoolinnean/zlac032
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic lineages, cryptic barriers: historical seascapes and oceanic fronts drive genetic diversity in supralittoral rockpool beetles (Coleoptera: Hydraenidae)

Abstract: Morphologically cryptic lineages confound many estimates of global biodiversity and are often discovered in ecologically specialized taxa, subject to strong morphological constraint. Such a situation may apply in many extreme environments, including supralittoral rockpools, where dramatic fluctuations in water availability and salinity impose strong selection pressures on the inhabitants. Here we explore the genetic diversity and phylogeography of supralittoral rockpool Ochthebius beetles in the eastern Atlant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 100 publications
2
8
0
Order By: Relevance
“…The absence of a detectable influence of distance may be attributed to either a recent range expansion or a notable homogenising effect of gene flow related to dispersal [ 29 ]. Notably, a recent expansion into the Mediterranean has been previously suggested for O. lejolisii , a species initially considered restricted to the Atlantic Sea [ 39 ]. At a larger spatial scale (hundreds of km), Villastrigo et al [ 38 ], using other molecular markers (COI and wingless), found a lack of significant relationships between genetic and geographical distance, suggesting that additional factors played a more important role in the genetic structure of Ochthebius populations, such as oceanic currents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation

Flight Dispersal in Supratidal Rockpool Beetles

Plaza-Buendía,
Mirón-Gatón,
García-Meseguer
et al. 2024
Insects
Self Cite
“…The absence of a detectable influence of distance may be attributed to either a recent range expansion or a notable homogenising effect of gene flow related to dispersal [ 29 ]. Notably, a recent expansion into the Mediterranean has been previously suggested for O. lejolisii , a species initially considered restricted to the Atlantic Sea [ 39 ]. At a larger spatial scale (hundreds of km), Villastrigo et al [ 38 ], using other molecular markers (COI and wingless), found a lack of significant relationships between genetic and geographical distance, suggesting that additional factors played a more important role in the genetic structure of Ochthebius populations, such as oceanic currents.…”
Section: Discussionmentioning
confidence: 99%
“…Coastal Ochthebius may passively disperse via the transport of eggs by endo- and epizoochory with seabirds that frequently occur in rockpools, although no cases of phoresy have been documented in these species [ 38 ]. However, passive dispersal through marine currents may be the main method by which these insects disperse as marine plankton over medium to large spatial scales [ 38 , 39 , 40 ]. Therefore, the population genetic structure of the two Ochthebius species was predicted from the general circulation pattern of Mediterranean marine currents and associated oceanic fronts [ 38 ].…”
Section: Introductionmentioning
confidence: 99%

Flight Dispersal in Supratidal Rockpool Beetles

Plaza-Buendía,
Mirón-Gatón,
García-Meseguer
et al. 2024
Insects
Self Cite
“…These adverse conditions are so challenging that only adapted species can thrive there [34,35]. In this context, the very small (1-2 mm) aquatic beetles of the worldwide distributed genus Ochthebius Leach, 1815 (Coleoptera: Hydraenidae) are capable of inhabiting these extreme environments, with some of them exhibiting cryptic diversity [36] and even partial sympatry with overlapping niches [16]. However, Ochthebius species are absent in the intertidal zone, where the area is regularly covered by water with periods of circadian, circatidal, or circalunadian rhythms, and its organisms have a series of adaptations to it (in addition to physiological ones, they can also present avoidance mechanisms, fixation structures, and mechanical resistance) [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Mapping distribution ranges and population boundaries in insects is a difficult task [39,40], particularly within cryptic species groups like the mentioned Mediterranean supralittoral species of the genus Ochthebius [35,36,[41][42][43]. In addition, many of these habitats face serious threats due to land use changes, such as coastal development [44], resulting in fragmentation and/or habitat loss that negatively impacts population connectivity and viability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation